Efektivitas Perasan Air Kunyit (Curcuma longa) terhadap Penurunan Intensitas Nyeri pada Pasien Gastritis - Nur Rahmah; Sudarman; Brajakson Siokal; Ernasari; Suci Hardiyanti Suharto Putri (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2026)
Gastritis ia a disease case that is include in the top ten most common diseases in indonesia. Turmeric juice is one of the non-pharmacological therapies that can reduce the pain scale in gastritis. This study aims to determine the effect of giving turmeric water juice on reducing gastritis pain at the Lilimori Health Center, Bulu Taba District, Pasangkayu Regency 2023. The sampling techniue used purposive sampling. The statistical tests in this study used the Wilcoxon Test and the Mann Whitney Test.. The results of the Wilcoxon statistical test between the effect of giving turmeric water juice on reducing pain obtained results for the control and intervention groups of 0.000. This means that the P Value is <0.05, thus it can be concluded that there is an average difference between the pretest and posttest from both the control and intervention groups. The results of the Mann Whitney statistical test for the effect of giving turmeric water juice on reducing pain showed that the results for the pretest group were 0.062, while the posttest group was 0.000. This means that the P Value in the pretest > 0.05, thus it can be concluded that there is no difference in the pain scale before and after giving turmeric water juice in the pretest data. Whereas in the Posttest the P-Value was <0.05, thus it was concluded that there was a decrease in the pain scale before and after giving turmeric water in the intervention group. The conclusion of this study is that giving turmeric water juice can reduce pain in gastritis patients. Therefore, through this research, people can apply this non-pharmacological therapy as a traditional treatment in reducing gastritis pain.